Local Village Product Innovation Strategy to Penetrate Regional Markets: A Case Study of Food Processing SMEs - Saripah; Sugiyanto (Greenation Research & Yayasan Global Resarch National, 2025)
This study examines local village product innovation strategies in penetrating regional markets through case studies of food processing SMEs. A qualitative research method with a case study approach was used to analyze five food processing SMEs in Central Java region. Data were collected through in-depth interviews, observations, and document analysis. The results show that effective innovation strategies include product diversification based on local raw materials, packaging quality improvement, halal and PIRT certification, and digital technology utilization for marketing. SMEs that successfully penetrated regional markets have characteristics of consistent product innovation, strong partnership networks, and adaptability to market demands. Branding strategies that emphasize local wisdom and product added value have proven to increase product competitiveness. This research recommends strengthening human resource capacity, capital access, and technology support as keys to successful regional market expansion.